Incidence and functional consequences of hMLH1 promoter hypermethylation in colorectal carcinoma - Herman, James G. (The National Academy of Sciences, 1998)
Inactivation of the genes involved in DNA mismatch repair is associated with microsatellite instability (MSI) in colorectal cancer. We report that hypermethylation of the 5′ CpG island of hMLH1 is found in the majority of sporadic primary colorectal cancers with MSI, and that this methylation was often, but not invariably, associated with loss of hMLH1 protein expression. Such methylation also occurred, but was less common, in MSI− tumors, as well as in MSI+ tumors with known mutations of a mismatch repair gene (MMR). No hypermethylation of hMSH2 was found. Hypermethylation of colorectal cancer cell lines with MSI also was frequently observed, and in such cases, reversal of the methylation with 5-aza-2′-deoxycytidine not only resulted in reexpression of hMLH1 protein, but also in restoration of the MMR capacity in MMR-deficient cell lines. Our results suggest that microsatellite instability in sporadic colorectal cancer often results from epigenetic inactivation of hMLH1 in association with DNA methylation.